PRISMA: Preferred Reporting Items for Systematic Reviews and Meta-Analyses - Moher, D; Liberati, A; Altman, DG (PLoS Med, 2009)
PRISMA is an evidence-based minimum set of items for reporting in systematic reviews and meta-analyses. PRISMA focuses on the reporting of reviews evaluating randomized trials, but can also be used as a basis for reporting systematic reviews of other types of research, particularly evaluations of interventions.
Keywords: THEME: Education management; ⚠️ Invalid DOI

Preferred reporting items for systematic review and meta-analysis protocols (prisma-p) 2015 statement - Moher, D.; Shamseer, L.; Clarke, M.; Ghersi, D.; Liberati, A.; Petticrew, M.; Shekelle, P.; Stewart, L. (Systematic Reviews, 2015)
Keywords: ___working_potential_duplicate; ❓ Multiple DOI

Preferred reporting items for systematic review and meta-analysis protocols (prisma-p) 2015 statement - Moher, D.; Shamseer, L.; Clarke, M.; Ghersi, D.; Liberati, A.; Petticrew, M.; Shekelle, P.; Stewart, L. (Systematic Reviews, 2015)
Keywords: ___working_potential_duplicate; auto_merged; ❓ Multiple DOI